Field Practice Experiences of Prospective Indonesian Language Teachers: Preparing for 21st-Century Education Challenges - Santi Oktarina (STAI Hubbulwathan Duri, 2024)
This study explores the experiences of prospective Indonesian language teachers during field practice in schools, focusing on their interactions with students, teachers, school management, infrastructure, and the learning process. Using a phenomenological approach, data were collected through in-depth interviews with eight pre-service Indonesian language teacher candidates. Qualitative analysis techniques were employed to extract comprehensive insights. Findings reveal that field experience practices are highly effective in preparing prospective teachers to become professional educators. Key themes emerged: (1) the critical role of field practice in fostering professionalism; (2) the necessity for advanced technological competencies to effectively engage Generation Z students; (3) the importance of maintaining harmonious interactions with students and teachers to support a conducive learning environment; and (4) the adherence to school regulations, emphasizing the principle of adapting to institutional norms. The study underscores the importance of field practice in equipping pre-service teachers with the skills and attitudes needed for 21st-century education. Emphasis on technological proficiency and relational skills highlights the evolving demands of teaching Generation Z. Adherence to institutional norms ensures alignment with professional standards. Field experience practice plays a pivotal role in shaping professional Indonesian language teachers. By mastering technological skills, fostering positive relationships, and respecting school regulations, prospective teachers are better prepared to meet the challenges of modern education. These findings contribute to the broader discourse on teacher training and professional development.